Evaluationoof0theoRole0ofoGabapentin0and/oroOmega-30in0Uremic Pruritusofor0PatientsoUndergoing0Hemodialysis0 - Hussein, Sinan Forat; Kadhim, Kadhim Ali; Al_Sultani, Ali Jassim; Hussain, Saad Abdulrahman (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2017)
Uremicopruritus,0isochronic0itchingothat0occursoin0patientsowith0advancedoor0 end-stage renal0disease.oIt0isoone0ofocommon0symptomsoinopatients00with00end-stage renal0 diseaseowith0approximatelyo60–90%0ofopatients0on0hemodialysis(HD) suffering0fromothis0problem. This study wasodesigned0to evaluate theoefficacy0and safety of prescribing Gabapentinoand0Omega-3 in combination or aloneofor0relieving uremicopruritus0in Iraqi patients undergoing0hemodialysis. The resultsoshowed0that all the threeoinvolved0regimens0(gabapentin, omega-3,0and the combinationoof0both drugs) had0significantly reduced the pruritus score. Furthermore,0theocombination0was significantlyosuperior0tooother0regimens in reducingopruritus 0score, owhile0no0significant effect0wasoobserved0by oallothe regimensoon0interleukin-6oor0on parathyroid hormone serum0levels.In Conclusion Gabapentin0100mgoplus01000mg0omega-30based fishooil capsules containing 120mg0DHA and0180mg0EPA isosuperior0to each drug alone0in reducing pruritus scoreoin0a0sample0of Iraqi0patients.